Fatty acid composition of fermented buffalo milk (dadih) as traditional probiotics - Saufani Iza Ayu; Marliyati Sri Anna; Palupi Eny; Handharyani Ekowati (BIO Web of Conferences)
Dadih is a fermented food containing bacteria that transform buffalo milk properties. The lactic acid bacteria (LAB) in dadih contribute to health promoting effects, including dietary fatty acid production. This research aims to assess the fatty acid distribution, total LAB, and antioxidant capacity of dadih. Samples were obtained from buffalo cattlefarmers and analyzed in two groups: fresh and microwave-heated dadih. Both samples were tested for fatty acid content, total LAB, and antioxidant capacity. The research findings showed an average fat content of 7.13% in fresh dadih and 7.23% in heated dadih. The heated dadih has a different fatty acid profile. The linoleic acid, omega-6, and omega-9 content increase due to heated dadih, whereas the omega-3 and eicosapentaenoic acid decrease slightly due to heating processes. The primary composition of dadih is palmitic and oleic acids, which are the most abundant fatty acids present. The antioxidant capacity of heated dadih was 6.13% lower than the 37.65% found in fresh dadih. The average total LAB counts 8.00 in fresh dadih and 7.74 log cfu/g in heated dadih. The microwave heating preserved the fatty acid composition but decreased the viability of LAB and negatively impacted certain antioxidant components.